PENGARUH CAPITAL INTENSITY, BEBAN KOMERSIAL, STRUKTUR MODAL, DAN PROFITABILITAS TERHADAP PAJAK PENGHASILAN BADAN (STUDI EMPIRIS PADA PERUSAHAAN PT PERTAMINA DAN ANAK PERUSAHAANNYA TAHUN 2020 - 2024) - Anida Aulia Sifa; Muhammad Nuur Farid Thoha (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to determine the effect of capital intensity, commercial expenses, capital structure, and profitability on corporate income tax. The population in this study was PT Pertamina and its subsidiaries in the period 2020-2024. The sampling technique in this study used a purposive sampling method and obtained 10 companies. The analysis technique used was multiple linear regression with statistical software program for special sciences (SPSS) version 22.0. The results of this study indicate that capital intensity and capital structure have a negative and significant effect on corporate income tax. Meanwhile, commercial expenses and profitability have a positive and significant effect on corporate tax income